2022
DOI: 10.1007/s11357-022-00682-5
|View full text |Cite
|
Sign up to set email alerts
|

Focus group study on perceptions and information needs regarding vaccines targeting the older population: a cross-country comparison in four European countries

Abstract: The increasing life expectancy leads to more older adults suffering from infectious diseases. Vaccines are available against diverse infections such as influenza, pneumococcal disease, herpes zoster and tetanus. However, vaccine acceptance is crucial for optimal preventive effect. The objective of the study is to perform a cross-country analysis of the perceptions and decision-making behaviour of older adults regarding vaccinations and their information needs. Focus groups with older adults were conducted in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Additionally, the primary care physician’s clinic was the second preferred location, emphasizing their crucial role in promoting vaccination uptake. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the primary care physician’s clinic was the second preferred location, emphasizing their crucial role in promoting vaccination uptake. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…For example, only 50.8% of older adults in the European Union received the influenza vaccine in 2021 [ 5 ]. A potential reason for this low vaccine uptake is a lack of awareness among older adults about which vaccines are available to them [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research underscores the pivotal role healthcare workers (HCW) play in facilitating vaccine acceptance among older adults [ 7 9 ]. Previously, we showed that older adults prefer to be informed by HCW on available vaccines [ 6 ]. It is observed that a significant factor influencing vaccine acceptance is the recommendation by an HCW.…”
Section: Introductionmentioning
confidence: 99%